Development of a reaction rate of chemistry module through a scientific approach to science - Tiurlina Siregar (Jurnal Pendidikan Kimia (JPKIM), 2023)
Module development is very important in chemistry learning. The lack of modules as teaching materials is an obstacle in learning chemistry, especially the reaction rate material. Therefore this study aims to develop and validate the feasibility of the chemistry module on the reaction rate material through a scientific approach, as well as to assess how students and teachers respond to the product being developed. The research and development (R&D) method is the method used and ADDIE is the development model applied as the methodology. The sample in this study was 15 students. The sampling technique is saturated samples. Modules are validated by material and media validators and then validated by teachers and asked for responses from students. Data is processed using SPPS Reaction rate as the subject of this research. The developed module is very feasible to be applied in chemistry learning on reaction rate material, according to the results of the data analyzed. The material validator gave an average score of 91.77% (very feasible), the media validator 90.48% (very feasible) and the teacher's response was 99.07% (very good) and the students' response to the developed module was 97.50% (Very good).Keywords: Chemistry; Module; Reaction rate; Scientific approach